Evaluating a wellness intervention including micro-practices for healthcare professionals before and during COVID-19 - Reyes-Chacón, Maria Teresa; Ramírez-Martínez, Flor Rocio; Márquez-Miramontes, Blanca; Leiner, Marie (Horizonte Sanitario, 2022)
Objective: To describe, with a mixed design study, healthcare professionals' pre-postdescriptive measures of quality of life (subjective wellness) and prolonged fatigue, as well asan improvement in overall wellness and satisfaction regarding micro-practices as a result ofparticipation in a wellness intervention before and during COVID-19.Material and Methods: This study had a mixed design involving two independent groups ofhealthcare professionals participating in a wellness intervention with micro-practices beforeand during COVID-19. The intervention contained multimodal presentations with animatedcartoon stories, comics, storytelling, readings, breathing, mindfulness and visualizationexercises, adapted from second-order factors in the Indivisible Self model. Pre-postdescriptive measures of quality of life (subjective wellness), prolonged fatigue, as well asimprovement in overall wellness and satisfaction regarding micro-practices were collected.Results: Attending to either wellness interventions before or during COVID-19 hada positive and, in some cases significant, effect on important indicators of quality-of-lifeand prolonged fatigue among healthcare professionals. A qualitative analysis indicateda subjective improvement in overall wellness and satisfaction regarding the use of micropracticesincluded in the wellness interventions, regardless of whether these were presentedin person or virtually. Most participants subjectively indicated that they improved in thetargeted indicators, especially achievement of better wellness.Conclusions: During ordinary and extraordinary circumstances, healthcare professionalsrequire specific interventions that act primarily to provide them with strategies that canimprove physical, emotional, and spiritual health. Use of micro-practices in multimodalworkshops to improve healthcare practitioner wellness is a successful tool for learning orremembering the importance of pausing during daily clinical activities and refocusing theirenergy.Keywords: Holistic health; Health care providers; Health promotion, Working Conditions.